ANALYSIS OF THE ROLE OF SANOLO VILLAGE GOVERNMENT IN FAMILY ECONOMIC WELFARE FROM A SHARIA ECONOMIC PERSPECTIVE (CASE STUDY OF SALT FARMERS IN SANOLO VILLAGE, BIMA REGENCY) - Eka; H.ihwan P. Syamsudin; Dinah Husniah (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the role of the Sanolo Village Government in improving the economic welfare of salt farming families in Sanolo Village, Bima Regency, from a sharia economic perspective. This research used a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation studies relevant to the socio-economic conditions of the salt farming community and village government policies. The results indicate that the Sanolo Village Government plays a significant role in supporting the improvement of family economic welfare through various empowerment programs, assistance with production facilities, and strengthening community economic institutions. From a sharia economic perspective, these efforts align with the principles of justice, welfare, and social responsibility, although several obstacles remain in their implementation, such as limited access to capital and fluctuations in salt prices. In conclusion, the village government plays a significant role in improving the economic welfare of salt farmers. However, strengthening sharia-based economic strategies is needed to create a more just, sustainable, and equitable welfare for the community.